2012
DOI: 10.1007/s11042-011-0983-y
|View full text |Cite
|
Sign up to set email alerts
|

Gesture-based interaction via finger tracking for mobile augmented reality

Abstract: The goal of this research is to explore new interaction metaphors for augmented reality on mobile phones, i.e. applications where users look at the live image of the device's video camera and 3D virtual objects enrich the scene that they see. Common interaction concepts for such applications are often limited to pure 2D pointing and clicking on the device's touch screen. Such an interaction with virtual objects is not only restrictive but also difficult, for example, due to the small form factor. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 45 publications
0
75
0
Order By: Relevance
“…This might mean that gestures that requires longer interaction times could face acceptance problems. For instance, one of the possible solutions that Hürst et al [8] suggested was to focus on applications that requires gestures less frequently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This might mean that gestures that requires longer interaction times could face acceptance problems. For instance, one of the possible solutions that Hürst et al [8] suggested was to focus on applications that requires gestures less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Other works, such as [8,17] partially addressed encumbrance issues due to multi-marker use by attaching color stickers on fingertips. Recently, Hürst et al [8] implemented various interaction capabilities on mobile phones by employing the system's sensor data, and color markers on fingertips.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is a very interesting method it is unable to move the VO and also rotating the head for manipulation can be tiresome. Hürst and van Wezel, [Hürst and van Wezel 2013] presented their research on potential of finger tracking for gesturebased interaction through two experiments. Their results indicated a high entertainment value, but low accuracy.…”
Section: Ar Interactionmentioning
confidence: 99%